Identification of Plankton Abundance as an Indicator of Water Quality in Intensive Vannamei Shrimp (Litopenaeus vannamei) Pond at PT. XYZ - I Gusti Putu Gede Rumayasa Yudana; Nazran Nazran; Ailsallwa Enggar Denisa (Eduvest - Journal of Universal Studies, 2026)
This research aims to identify plankton abundance as a supporting indicator of water quality in intensive white leg shrimp (Litopenaeus vannamei) ponds at PT. XYZ. The research applied a descriptive method using survey, field observation, interviews, direct participation, and analysis of primary and secondary data. Plankton observation was conducted using a hemocytometer with big block and small block counting methods, while water quality was assessed through transparency, water color, dissolved oxygen (DO), pH, ammonium (NH4), and nitrite (NO2) parameters. The identification results showed that the plankton groups found consisted of Chlorophyta, Cyanophyta, Bacillariophyta, Pyrrophyta, Cryptophyte, and Protozoa. Chlorophyta was the most dominant group, ranging from 30–80%, followed by Pyrrophyta at 20–36%, Cyanophyta at 3–26%, Bacillariophyta at 1–28%, and Protozoa at 1–5%. The DO values ranged from 4.6–6.38 mg/L, while pH values ranged from 7.9–8.5, indicating that both parameters remained suitable for plankton and shrimp growth. However, ammonium and nitrite concentrations exceeded the optimal standards, suggesting organic matter accumulation from uneaten feed and shrimp feces. Therefore, plankton abundance can serve as an important biological indicator for monitoring water quality in intensive shrimp pond management.